Financial support for the development of green tourism - Davydenko Nadiia; Abuselidze George; Horb Kostiantyn; Sylenko Mykola (BIO Web of Conferences)
Socio-economic risks, environmental disasters, environmental pollution and wars force countries to implement policies aimed at protecting the environment and improving the living conditions of the population. These challenges are becoming increasingly urgent as global climate change, population growth and industrialization increase the negative impact on ecosystems and human health. The principles of environmental policy are gradually being integrated into business strategies, which has led to the emergence of a new type of entrepreneurial activity - green tourism. The purpose of the article is to identify the main problems and specifics of financial support further development of green tourism in Ukraine. Considering this, the tasks of the work are: substantiating the main goals of financial support for the development of green tourism in Ukraine, conducting an analysis of the state of financing and substantiating the main areas of improvement and ways to solve the identified problems. The article analyzes the importance of financial support for the development of green tourism. The main directions for improving the financial support for the functioning of the tourism industry are proposed.